HUBUNGAN NILAI NATRIUM SERUM DENGAN LUARAN FUNGSIONAL PADA PASIEN CEDERA KEPALA - Riezky Valentina Astari,* Jimmy Eko Budi Hartono,** Dody Priambada*** (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION SODIUM LEVEL DISTURBANCE IS COMMON AFTER TRAUMATIC BRAIN INJURY AND MAY CAUSE SERIOUS COMPLICATIONS AND POOR OUTCOME INCLUDING DEATH SODIUM PLAY A ROLE IN CYTOTOXIC PROCESS AND REPERFUSION PATHWAY IN SECONDARY BRAIN DAMAGE SERUM SODIUM LEVEL AND ITS RELATIONSHIP WITH OUTCOME IN BRAIN INJURY IS SCARCELY STUDIED